The Traitors' Gate - Avi, 1937- (Atheneum Books for Young Readers, 2007)
When his father is arrested as a debtor in 1849 London, fourteen-year-old John Huffman must take on unexpected responsibilities, from asking a distant relative for help to determining why people are spying on him and his family.